2006
DOI: 10.1261/rna.241006
|View full text |Cite
|
Sign up to set email alerts
|

Translation-independent inhibition of mRNA deadenylation during stress in Saccharomyces cerevisiae

Abstract: Post-transcriptional control mechanisms play an important role in regulating gene expression during cellular responses to stress. For example, many stresses inhibit translation, and at least some stresses inhibit mRNA turnover in yeast and mammalian cells. We show that hyperosmolarity, heat shock, and glucose deprivation stabilize multiple mRNAs in yeast, primarily through inhibition of deadenylation. Although these stresses inhibit translation and promote the movement of mRNAs into P-bodies, we also observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
98
1
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(107 citation statements)
references
References 36 publications
7
98
1
1
Order By: Relevance
“…4,20) Here we found that ethanol stress also enhanced the formation of P-bodies in sake yeast as well as laboratory strains in SD medium (Fig. 1A), and that elimination of the ethanol rapidly caused the disassembly of P-bodies (Fig.…”
Section: Discussionmentioning
confidence: 62%
“…4,20) Here we found that ethanol stress also enhanced the formation of P-bodies in sake yeast as well as laboratory strains in SD medium (Fig. 1A), and that elimination of the ethanol rapidly caused the disassembly of P-bodies (Fig.…”
Section: Discussionmentioning
confidence: 62%
“…For example, both nuclear pre-mRNA and cytoplasmic mRNA polyadenylation can be regulated during the cell cycle (Colgan et al 1996;Groisman et al 2006) and in response to certain signaling events (Wu et al 1998;Mellman et al 2008). Moreover, poly(A) dynamics are also regulated by environmental stress (Hilgers et al 2006) and by miRNAs (Wu et al 2006). We speculate that CPEB activity may be necessary for maintaining steady state p53 levels under normal conditions where it has important functions in cellular aging and energy metabolism (Bensaad and Vousden 2007).…”
Section: Discussionmentioning
confidence: 97%
“…It has been shown that thiolutin induces some stress in yeast cells (Grigull et al, 2004) and that stress induces mRNA stabilization (reviewed in Bond, 2006). However, the stress stabilization of mRNA occurs by inhibition of deadenylation (Hilgers et al, 2006), hence the effect of thiolutin cannot be an indirect consequence of the stress. Thiolutin also has an inhibitory effect on translation at high concentrations (Jiménez et al, 1973) and it is known that inhibition of translation blocks mRNA degradation at the level of decapping, without inhibiting deadenlylation (Beelman and Parker, 1994).…”
Section: Discussionmentioning
confidence: 99%